Diseño del proceso de extracción y fitomejoramiento del cannabis para producción de aceite CBD para la industria cosmética. (2022)
This work is done with the purpose of identifying development opportunities in a sector that is currently experiencing exponential growth, which is the Cannabis market. Therefore, the main objective is to make a design proposal for CBD oil extraction for the cosmetic industry through solid-liquid extraction. To further contextualize the process, the generalities of the plant in terms of existing Cannabis species were identified along with their respective components in order to know their different benefits and disadvantages. Likewise, emphasis was placed on the cultivation and breeding parameters that a plant can have in terms of genetic improvement and cultivation conditions so that in this way the process is more deeply understood in order to continue with the extraction method that favors yield. of the product to be obtained. Regarding the selection of the extraction method, thanks to the different studies, bibliographical research and courses carried out, a comparative study was carried out regarding procedures, process variables, determination of equipment to be used, raw materials, operating conditions, etc. A chemical route matrix is ​​made to select the method that is most convenient in the investigation to subsequently design the appropriate extraction process to obtain CBD oil.